Efficacy of Oral Etoposide in Pretreated Metastatic Breast Cancer. Issue 17 (May 2015) - Yuan, Peng; Di, Lijun; Zhang, Xiaohui; Yan, Min; Wan, Donggui; Li, Li; Zhang, Yongqiang; Cai, Jufen; Dai, Hong; Zhu, Qi; Hong, Ruoxi; Xu, Binghe; et al.
<x xml:space="preserve">Abstract</x> Abstract No standard chemotherapy has been defined for metastatic breast cancer (MBC) patients pretreated with anthracyclines and taxanes. A multicenter phase 2 study was conducted to evaluate the safety and efficacy of oral etoposide in patients with MBC. Eligible patients were treated with repeated cycles of oral etoposide (60 mg/m2/d on days 1–10, followed by 11 days of rest). The primary endpoint was progression-free survival (PFS). The secondary endpoints were objective response rate, clinical benefit rate (CBR), and toxicity profiles. Seventy-five women with MBC were enrolled at 10 centers in China. Seven (9.3%) patients achieved partial response (PR) and 29 (38.7%) had stable disease (SD). Nine patients (12%) had SD for >24 weeks and the CBR was 21.3% (16/75). The median PFS was 4.5 (range, 1.3–7.7) months. Of the 38 patients who received ≥3 regimens prior to this study, 2 (5.3%) had PR and 3 (7.9%) had SD for >24 weeks, with a CBR of 13.2%. The reported grade 3/4 adverse events included leukopenia (13.3%, n = 10), neutropenia (17.9%, n = 14), anemia (2.7%, n = 2), vomiting (2.6%, n = 2), and alopecia (1.3%, n = 1). Oral etoposide was effective and well tolerated in Chinese women with pretreated MBC.